2021
DOI: 10.1186/s13037-021-00308-3
|View full text |Cite
|
Sign up to set email alerts
|

Variation in practice for preoperative antibiotic prophylaxis: a survey from an academic tertiary referral center in the United States

Abstract: Background Antibiotic surgical prophylaxis is a core strategy for prevention of surgical site infections (SSI). Despite best practice guidelines and known efficacy of antibiotic prophylaxis in decreasing SSI risk, there is often wide variation in its use. This study was designed to determine the individual perspectives of perioperative providers at an academic tertiary referral center regarding their knowledge of preoperative antibiotic choice, dosing, and timing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Antibiotic prophylaxis is one of the most crucial methods to decrease the risk of SSI incidence. 3 Previous studies showed that patients with SSI had twice the chance of dying, five times the chance of being readmitted, and a 60% increased chance of being committed to the intensive care unit (ICU). 4 Perioperative antibiotic prophylaxis (PAP) is provided to avoid local or systemic infection, such as SSI, UTI, or sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic prophylaxis is one of the most crucial methods to decrease the risk of SSI incidence. 3 Previous studies showed that patients with SSI had twice the chance of dying, five times the chance of being readmitted, and a 60% increased chance of being committed to the intensive care unit (ICU). 4 Perioperative antibiotic prophylaxis (PAP) is provided to avoid local or systemic infection, such as SSI, UTI, or sepsis.…”
Section: Introductionmentioning
confidence: 99%